IT-143, A Polymer Micelle Nanoparticle, Widens Therapeutic Window of Daunorubicin - Lee Costich, Tara; Carie, Adam; Semple, J. Edward; Sullivan, Brad; Vojkovsky, Tomas; Ellis, Tyler; Buley, Taylor; Bakewell, Suzanne; Sill, Kevin (Pharmaceutical Nanotechnology, 2016)
Background: Daunorubicin is an anthracycline family chemotherapeutic indicated for the treatment of acute myelogenous and acute lymphoblastic leukemia. Daunorubicin has a narrow therapeutic window. Objective: To extend circulation time, decrease toxicity and improve the efficacy of daunorubicin, we encapsulated the drug in our nanoparticle drug delivery platform. Method: IT-143 is a lyophilized formulation of daunorubicin, non-covalently encapsulated in the hydrophobic core of a polymer micelle. Hydroxamic acid-containing triblock polymers (ITP-102) support ferric crosslinking between the polymer chains, increasing stability for improved drug circulation and allowing a tumor targeted pH dependent release of the encapsulated daunorubicin. Results: Formulation characterization demonstrates a 3.7% weight loading (w/w) of daunorubicin and an average particle diameter of 58 nm. IT-143 has an in vitro cytotoxicity of 60-100 nM, comparable to free drug cytotoxicity of 67-114 nM. We compared daunorubicin pharmacokinetics between free drug and IT-143 in vivo and the maximum serum concentration of daunorubicin from IT-143 was increased 50-fold. At equivalent doses IT-143 eliminated in vivo gross toxicity observed at daunorubicin’s maximum tolerated dose of 7.5 mg/kg, and increased the equitoxic dose to 17.5 mg/kg. Furthermore, IT-143 improved anti-tumor efficacy. Studies in 3 xenograft models (HCT116, HT-1080 and MNNG-HOS) compared intravenous bolus administration of IT-143 at equivalent and equitoxic doses to daunorubicin treatment. IT-143 increased the inhibition of tumor volume growth in all models. Conclusion: These studies indicate that the encapsulation of daunorubicin by IT-143 widens the therapeutic window of daunorubicin treatment with reduced toxicity and increased antitumor efficacy.
Keywords: in vivo efficacy